Microbiological, chemical and sensory spoilage analysis of raw Atlantic cod (Gadus morhua) stored under modified atmospheres. (April 2018) - Kuuliala, L.; Al Hage, Y.; Ioannidis, A.-G.; Sader, M.; Kerckhof, F.-M.; Vanderroost, M.; Boon, N.; De Baets, B.; De Meulenaer, B.; Ragaert, P.; Devlieghere, F.
Abstract: During fish spoilage, microbial metabolism leads to the production of volatile organic compounds (VOCs), characteristic off-odors and eventual consumer rejection. The aim of the present study was to contribute to the development of intelligent packaging technologies by identifying and quantifying VOCs that indicate spoilage of raw Atlantic cod ( Gadus morhua ) under atmospheres (%v/v CO2 /O2 /N2 ) 60/40/0, 60/5/35 and air. Spoilage was examined by microbiological, chemical and sensory analyses over storage time at 4 or 8 °C. Selected-ion flow-tube mass spectrometry (SIFT-MS) was used for quantifying selected VOCs and amplicon sequencing of the 16S rRNA gene was used for the characterization of the cod microbiota. OTUs classified within the Photobacterium genus increased in relative abundance over time under all storage conditions, suggesting that Photobacterium contributed to spoilage and VOC production. The onset of exponential VOC concentration increase and sensory rejection occurred at high total plate counts (7–7.5 log). Monitoring of early spoilage thus calls for sensitivity for low VOC concentrations. Highlights: Microbiological, chemical and sensory spoilage analyses for Atlantic cod. Volatile organic compounds (VOCs) were quantified in real time during storage. Photobacterium phosphoreum likely contributed to spoilage under all conditions. Several potential spoilage indicators were identified. Sensitivity for low VOC concentrations is essential for monitoring early spoilage.